(3agQSJ ELGRGJ eTGjN OeTbs - (3EHQGgje Hf eQGO GdMfaj GdCRgQjs ((3eMeO eQJVi GdMSjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bSe dCgd GdMOjK ef GdNjQ ChaQ fUjH hRGO s
(3BNQgG (B:s
(3Yf eMeO Hf YHO GdbGOQ GdaGSi s
(3hgj ELGRGJ ef (B: (3YHO GdZfi GdfGHdSi , YHO GdHGbi Hf YHO GdQMef He eZjRd , edG EdjGS GdchQGfi , CMeO Hf YHO GdQcje GdZRi , YHO GdSdGe Hf eMeO GdcGedi , ehSi Hf CHj GdSYhO GdeMGSfi GdMfai , eMeO Hf YHO GdLdjd Hf CHj GdehGgH , YHO GdMef GdSdjei GdeLdOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdJGQjN (B- (3bSe (B4 - (3U (B319 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI HZOGO (B(62) s
Keywords: (3GdJGQjNs